2008
DOI: 10.1007/s11270-008-9683-2
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Plant Species with the Potential for the Phytoremediation of Arsenic and Metals Contaminated Soil

Abstract: Here we present results of a survey conducted to identify and characterize spontaneously growing arsenic-tolerant plant species of the area around the old arsenic/gold mine in ZlotyStok (Poland), with respect of their potential use in phytoremediation. Plants and soil from their rhizosphere were sampled and analyzed for concentrations of As and accompanying Mn, Fe, Mg, Ca, Al, Cu, Zn, Ba, Pb, Ni, Cs, V, Cr, Sr, Rb, Bi, Mo and U. The soil contained primarily very high As, Pb and Al concentrations (up to 7,451, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Arsenic mining is one example of these activities, as soil and water around mines contain increased concentrations of arsenic as well as heavy metals (Antosiewicz et al 2008;Sridhar et al 2007). In addition, several studies have reported a high degree of arsenic and/or heavy metal pollution in soils affected by the oxidation of pyritic materials (Alvarenga et al 2004;Antosiewicz et al 2008;Moreno-Jiménez et al 2009.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Arsenic mining is one example of these activities, as soil and water around mines contain increased concentrations of arsenic as well as heavy metals (Antosiewicz et al 2008;Sridhar et al 2007). In addition, several studies have reported a high degree of arsenic and/or heavy metal pollution in soils affected by the oxidation of pyritic materials (Alvarenga et al 2004;Antosiewicz et al 2008;Moreno-Jiménez et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic mining is one example of these activities, as soil and water around mines contain increased concentrations of arsenic as well as heavy metals (Antosiewicz et al 2008;Sridhar et al 2007). In addition, several studies have reported a high degree of arsenic and/or heavy metal pollution in soils affected by the oxidation of pyritic materials (Alvarenga et al 2004;Antosiewicz et al 2008;Moreno-Jiménez et al 2009. The risks for both environment and human health from arsenic and toxic heavy metals (specifically Cd, Cr, Cu, Ni, Pb, and Zn) are associated with the forms bioavailable to plants ( Kabata-Pendias 2004;Zhao et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it is always more appropriate to use local species for phytoremediation than exotic plants (Yoon et al 2006;Antosiewicz et al 2008;Barrutia et al 2009;Marques et al 2009b), seeds of plants characteristic of this area were chosen: Medicago sativa (alfalfa), Trifolium incarnatum (red clover) and a mix of seeds for forage. Alfalfa has the capacity to accumulate metal(oid)s above the tolerance levels of other plants and has the characteristics required by a plant for the extraction from contaminated water and soil (Peralta-Videa et al 2001).…”
Section: Soil Contamination By As Co Cr and Pb In An Alpine Territomentioning
confidence: 99%